Study of the reaction of the choice of combat athletes using computer technology - Vyacheslav Romanenko; Svitlana Piatysotska; Yuriy Tropin; Łukasz Rydzik; Valerii Holokha; Natalia Boychenko (Kharkiv State Academy of Physical Culture, 2022)
Purpose: to develop a methodology for evaluating the reaction of the choice of combat athletes using computer technologies and to conduct research on testing and determining its validity. Materials, participants and methods: the total number of participants in the study was 77 people (mean age: 13.8±0.7 years, 28% girls, 72% boys). To evaluate the choice reaction, the computer program «Visuomotor Choice Reaction» for mobile devices was developed and implemented. The following methods have been studied: analysis of scientific and methodological information and Internet sources; summarizing best practices; computer programming method; methods of mathematical statistics. Results: the study was carried out in three stages. At the first stage, the correspondence of the selected colors and shapes to the tasks that should be solved during the test was determined. Measuring the speed of response to a single color and to individual shapes showed that the values are evenly distributed, the range of variation for the response to color was 50,7 ms, and the response to shapes was 133,4 ms. At the second stage, indicators of the reaction of choice were obtained and the operation of the computer program was tested in the "field conditions". The practical application of the program made it possible to obtain indicators of the reaction of the choice of taekwondo novice athletes and determine the stability of its work. The obtained data of the third stage determined the reliability and validity of the proposed method for assessing the reaction of choice. Conclusions: based on the analysis of scientific and methodological literature and the competitive activity of martial artists of various specializations, conversations with coaches and qualified athletes, a computer program «Visuomotor Choice Reaction» was developed to assess the choice reaction. According to the results of the study of the reaction of choice of taekwondo novice athletes using the proposed methodology, in order to test it, it can be argued that the «Visuomotor Choice Reaction» computer program allows you to obtain indicators of sensorimotor reactions, is simple and reliable when using it. According to the results of the correlation and dispersion analysis, it can be argued that the proposed method for assessing the choice reaction is reliable and has a significant level of validity and meets all metrological requirements.